Consumer Green Purchases in the New Normal Condition of The Covid-19 Pandemic - A. Nurul Suci Amaliah; Mardiatul Jannah; Nindya Dewi Rizka Sari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
After the COVID-19 pandemic, more consumers were concerned about their health and the environment. This condition also positively affects the environmental awareness of consumers and can be a significant factor influencing customers to purchase green products. This study identified potential factors affecting green products purchase as consumer actual behavior. The main predictors are the impact of the COVID-19 Pandemic, environmental attitude, and environmental awareness and moderated by green product literacy to predict actual behaviour by purchasing the green product in the new normal era. In this way, it will help policymakers and managers for formulating and implement to encourage green purchasing and comprehension of green consumerism, especially in the Asian market. This study conducted with survey with purposive sampling method and analyzed data by SEM PLS for the hypotheses test. The number of valid observations for the data analysis is 100. The result of algorithm testing found the data was valid and reliable, as well as the framework accurate (Model Fit). Based on direct hypothesis testing, it was found that the impact of the pandemic is a significant factor in predicting environmental awareness (H1). Meanwhile the impact of the pandemic not significantly predicts green product purchases (H2). Furthermore, environmental awareness finding as a significant factor influence green product purchases (H3). The other direct hypotheses also show environmental attitude as a significant factor to identify green product purchase (H5) while green product literacy was not supported as a significant factor in green product purchase (H6). On the other hand, specific indirect effect testing shows that environmental awareness successfully mediates the impact of pandemic on green product purchases (H4). For moderate testing, green product literacy moderates the relationship of environmental attitude to green product purchase (H7). The outcomes contribute and offer valuable information for future public policy and marketing campaigns regarding green product purchases.